2014
DOI: 10.1007/s10853-014-8735-9
|View full text |Cite
|
Sign up to set email alerts
|

Mn substitution-induced revival of the ferroelectric antiferromagnetic phase in Bi1−x Ca x FeO3−x/2 multiferroics

Abstract: Room-temperature X-ray diffraction, piezoresponse force microscopy, and SQUID magnetometry measurements of the Bi 0.9 Ca 0.1 Fe 1-y Mn y O 3 (0 B y B 0.5) ferromanganites have been carried out to illustrate the effect of B-site substitution on the crystal structure and multiferroic properties of the Ca-doped compound representing an intermediate ferroelectric and weak ferromag-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…These observations are consistent with the suggestion of Schiemer et al [36] that macroscopic strains do not modify the cycloidal ordering, but local strain fields generated by lattice defects can act to suppress coupling between gradients of the magnetic order parameter and stabilize the symmetry-permitted [10] weak ferromagnetic state. The scenario of defect-driven magnetic transformation explains the difference in magnetic properties characteristic of the Bi 1-x Pr x FeO 3 [37] and Bi 1-x Ca x FeO 3-x/2 [30] perovskites (contrary to the former, the latter, having vacancies in the anion sublattice, exhibits a purely weak ferromagnetic behavior near the morphotropic phase boundary; elimination of lattice defects in the Ca-doped BiFeO 3 restores the antiferromagnetic order [38]). The possibility to control the magnetic ground state of BiFeO 3 via inducing/eliminating lattice defects could pave the way toward innovative magnetoelectric functionality.…”
Section: Resultsmentioning
confidence: 95%
“…These observations are consistent with the suggestion of Schiemer et al [36] that macroscopic strains do not modify the cycloidal ordering, but local strain fields generated by lattice defects can act to suppress coupling between gradients of the magnetic order parameter and stabilize the symmetry-permitted [10] weak ferromagnetic state. The scenario of defect-driven magnetic transformation explains the difference in magnetic properties characteristic of the Bi 1-x Pr x FeO 3 [37] and Bi 1-x Ca x FeO 3-x/2 [30] perovskites (contrary to the former, the latter, having vacancies in the anion sublattice, exhibits a purely weak ferromagnetic behavior near the morphotropic phase boundary; elimination of lattice defects in the Ca-doped BiFeO 3 restores the antiferromagnetic order [38]). The possibility to control the magnetic ground state of BiFeO 3 via inducing/eliminating lattice defects could pave the way toward innovative magnetoelectric functionality.…”
Section: Resultsmentioning
confidence: 95%
“…The results support the conclusions of the It has been recently shown that the magnetic properties of BiFeO 3 -based multiferroics can be influenced by structural defects. [16][17][18][51][52][53] Indeed, even a small deviation from the ideal cation-anion stoichiometry that results in the appearance of lattice defects can trigger the removal of the cycloidal magnetic order, thus giving rise to a weak ferromagnetic behavior. 54 Taking into consideration that the distribution/concentration of the defects affects the ferroelectric domain structure of a material, 55 The magnetic structure of BiFeO 3 is stabilized by the antisymmetric Dzyaloshinskii-Moriya (DM) interaction of the form…”
Section: 42mentioning
confidence: 99%
“…The origin of the Ca 2+ substitution-driven instability of the cycloidal order has been shown to be closely connected with the charge-compensatory mechanism that involves the formation of anion vacancies in the acceptor-doped materials. [16][17][18] Nevertheless, the doping-introduced lattice defects seem not to be the only factor determining the evolution of magnetic properties in the Bi 1Àx Ae x FeO 3Àx/2 series. Indeed, the Bi 1Àx Ba x FeO 3Àx/2 ferroelectrics have been proven to be antiferromagnetic, thus suggesting that the size of an alkali-earth substituent should also play an important role.…”
mentioning
confidence: 99%
“…Improved magnetic behavior and the coupling between the electric and magnetic ordering parameters alone are often not enough for potential device applications because regions where the ferroelectric polarization has been switched are at times unstable and do not stay in their switched state, but relax back to the original state. This process is known as “retention failure” and can lead to a loss of functionality of the device .…”
Section: Introductionmentioning
confidence: 99%
“…13 Perovskite oxides such as BiFeO 3 become even more versatile through the incorporation of substitutional elements on the A (Bi) or B-site (Fe), which enables us to manipulate and design the electronic and magnetic properties within certain limitations. 14,15 Ca as an A-site dopant has been shown to tune the material's behavior from antiferromagnetic toward ferromagnetic 16 but also to enhance the magnetoelectric coupling 17 and to enable a conductivity modulation through the application of an electric field. 18 Ca doping in BiFeO 3 can induce oxygen vacancies because the replacement of Bi 3+ with Ca, which is an alkaline earth metal and therefore cannot have a higher oxidation state than 2+, has a hole doping effect.…”
Section: Introductionmentioning
confidence: 99%